Issues of improving the use of livestock pastures - Badamdorj, Batkhishig (Studia Philosophiae Et Juris, 2023)
In the article the author considers the issue of pasture overloading as one of the most urgent problems of livestock breeding in Mongolia. The article consists of two parts. In the first part, the author characterizes the current state of pasture use and shows how overloaded pastures are and what are the main causes of pasture overloading and its consequences. In the second part, the author suggests some ways to reduce the overloading of pastures, such as introducing the law on payment for pasture use, improving pasture management, regulating the number of livestock by increasing domestic consumption and export of meat and others. Малын бэлчээр ашиглалтыг сайжруулах асуудал Хураангуй Бэлчээрийн мал аж ахуй бол түүний үндсэн нөхцөл болох бэлчээр, түүний усжуулалт, мал эмнэлэг, мал зүй гээд олон хүчин зүйлээс бүрэлдэн хамаарах үйлдвэрлэлийн цогц систем юм. Гэхдээ энэхүү өгүүлэлд мал аж ахуйн үйлдвэрлэлийн үндсэн нөхцөл болох бэлчээрийн ашиглалтыг сайжруулах асуудлыг онцлон авч үзэв. Tүлхүүр үгс: бэлчээрийн даац, бэлчээрийн төлбөр, бэлчээрийн менежмент